Menstrual cycle phase and carbohydrate ingestion alter immune response following endurance exercise and high intensity time trial performance test under hot conditions - Hashimoto, H.; Ishijima, T.; Hayashida, H.; Suzuki, K.; Higuchi, M. (Journal of the International Society of Sports Nutrition, 2014)
Background: Sex hormones are known to regulate some responses during exercise. Evaluation of the differences in exercise response with regard to menstrual cycle will help understand the menstrual cycle phase specific adaptations to exercise and athletic performance.